CT-guided percutaneous biopsy of suspect pancreatic lesions: radiological and clinical outcome. Issue 11 (November 2019) - Gruber-Rouh, T.; Langenbach, M.C.; Eichler, K.; Vogl, T.J.; Yel, I.; Beeres, M.
Abstract : AIM: To evaluate the clinical utility of computed tomography (CT)-guided percutaneous biopsies of suspect pancreatic lesions regarding safety, efficiency, radiation dose, intervention time, diagnostic yield, and complications. MATERIALS AND METHODS: Between 2015 and 2018, 48 patients (18 female, 30 male; mean age: 64.2 years) with suspect pancreatic lesions underwent CT-guided percutaneous biopsy. Ultrasound-guided biopsy of all lesions was not possible or without any result. CT-guided interventions were compared according to the following intervention parameters: radiation dose, procedure duration, number of needle correction scans. Evaluation criteria included technical success as well as major and minor complications according to the Society of Interventional Radiology. RESULTS: Biopsies were performed successfully in 100% of patients. No major side effects occurred during intervention. As a minor complication, 29.2% showed focal haemorrhage. Seventy-seven percent of lesions had a malignant appearance, and benign inflammatory lesions were found in 23%. The mean size of the target lesions was 2.9 cm (range: 0.7–2.3 cm). The mean target access path within the patient was 8 cm (range: 3–14 cm). The duration to completion was 12 minutes (range: 3 minutes 30 seconds to 30 minutes). The dose–length product of the intervention was 89.5 mGy·cm (range: 11–350 mGy·cm). The average number needle correction scans was 31.1 (range: 6–36). CONCLUSION: CT-guided biopsy of suspect pancreatic lesions is an efficient and safe method. It can be performed within short intervention times and low radiation exposure for differentiation of unclear lesions. Highlights: CT-guided biopsies of pancreas are an effective method for diagnosis of pancreatic cancer. CT-guided biopsies of pancreas is a safe intervention, which is successful in all cases without any major complications. CT-guiding can be performed with short intervention times and low radiation exposure.